Secretion of Gluconic Acid From Nguyenibacter sp. L1 Is Responsible for Solubilization of Aluminum Phosphate - Li, Xiao Li; Zhao, Xue Qiang; Dong, Xiao Ying; Ma, Jian Feng; Shen, Ren Fang (Frontiers in Microbiology, 2021)
Phosphorus (P) deficiency is one of the major factors limiting plant growth in acid soils, where most P is fixed by toxic aluminum (Al). Phosphate-solubilizing bacteria (PSBs) are important for the solubilization of fixed P in soils. Many PSBs have been isolated from neutral and calcareous soils, where calcium phosphate is the main P form, whereas PSBs in acid soils have received relatively little attention. In this study, we isolated a PSB strain from the rhizosphere of Lespedeza bicolor, a plant well adapted to acid soils. On the basis of its 16S rRNA gene sequence, this strain was identified as a Nguyenibacter species and named L1. After incubation of Nguyenibacter sp. L1 for 48 h in a culture medium containing AlPO4 as the sole P source, the concentration of available P increased from 10 to 225 mg L-1, and the pH decreased from 5.5 to 2.5. Nguyenibacter sp. L1 exhibited poor FePO4 solubilization ability. When the pH of non-PSB-inoculated medium was manually adjusted from 5.5 to 2.5, the concentration of available P only increased from 6 to 65 mg L-1, which indicates that growth medium acidification was not the main contributor to the solubilization of AlPO4 by Nguyenibacter sp. L1. In the presence of glucose, but not fructose, Nguyenibacter sp. L1 released large amounts of gluconic acid to solubilize AlPO4. Furthermore, external addition of gluconic acid enhanced AlPO4 solubilization and reduced Al toxicity to plants. We conclude that secretion of gluconic acid by Nguyenibacter sp. L1, which is dependent on glucose supply, is responsible for AlPO4 solubilization as well as the alleviation of Al phytotoxicity by this bacterial strain.